DIGITAL WALLET USAGE AND ITS INFLUENCE ON PERSONAL FINANCIAL PLANNING AMONG MILLENNIALS - PA Andiena Nindya Putri; Irdawati Irdawati; Billy Dewantara; Upik Djaniar; Fitriani Fitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Millennials are considered the most tech-savvy generation, having grown up in an era characterized by rapid technological evolution and internet proliferation. This familiarity with digital interfaces has naturally extended into their financial behaviors, including their preferences for digital payment systems. The objective of this research is to analyze the usage of digital wallets and their influence on personal financial planning among millennials. This study adopts a systematic literature review (SLR) approach to comprehensively analyze and synthesize prior studies regarding the use of digital wallets and their influence on personal financial planning among millennials. This literature review has explored the relationship between digital wallet usage and personal financial planning among millennials, a generation characterized by high digital literacy and growing financial independence.